Children's Safety Initiative: A National Assessment of Pediatric Educational Needs among Emergency Medical Services Providers. (3rd April 2015) - Hansen, Matthew; Meckler, Garth; Dickinson, Caitlyn; Dickenson, Kathryn; Jui, Jonathan; Lambert, William; Guise, Jeanne-Marie
Abstract: Objective. Emergency medical services (EMS) providers may have critical knowledge gaps in pediatric care due to lack of exposure and training. There is currently little evidence to guide educators to the knowledge gaps that most need to be addressed to improve patient safety. The objective of this study was to identify educational needs of EMS providers related to pediatric care in various domains in order to inform development of curricula.Methods. The Children's Safety Initiative-EMS performed a three-phase Delphi survey on patient safety in pediatric emergencies among providers and content experts in pediatric emergency care, including physicians, nurses, and prehospital providers of all levels. Each round included questions related to educational needs of providers or the effect of training on patient safety events. We identified knowledge gaps in the following domains: case exposure, competency and knowledge, assessment and decision making, and critical thinking and proficiency. Individual knowledge gaps were ranked by portion of respondents who ranked them "highly likely" (Likert-type score 7–10 out of 10) to contribute to safety events.Results. There were 737 respondents who were included in analysis of the first phase of the survey. Paramedics were 50.8% of respondents, EMT-basics/first responders were 22%, and physicians 11.4%. The top educational priorities identified in the final round of the survey include pediatric airway management, responder anxiety when working with children, and general pediatric skills among providers. The top three needs in decision-making include knowing when to alter plans mid-course, knowing when to perform an advanced airway, and assessing pain in children. The top 3 technical or procedural skills needs were pediatric advanced airway, neonatal resuscitation, and intravenous/intraosseous access. For neonates, specific educational needs identified included knowing appropriate vital signs and preventing hypothermia.Conclusions. This is the first large-scale Delphi survey related to pediatric prehospital education. Our results provide foundational information related to the educational needs of prehospital providers. Medical directors and educators can use the results to shape future curricular development.